Scoreline effect on work-rate in English premier league soccer - Clark, P. D.; O'Donoghue, P. G. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The evidence that scoreline influences work-rate in elite soccer comes from a study where data were gathered from matches played in the 1997-98 season (1). Rule changes in soccer and player preparation have changed in the period since. Therefore, there is a need for up-to-date research into the influence of scoreline. The purpose of the current investigation was to apply the method used in previous research (1) to soccer performances in the 2009-2010 season. Methods A computerized time-motion analysis system was used to record the entire on-field activity of 20 players using 7 broad movement classes. High intensity activity included running / sprinting, backwards / sideways or on-the-spot shuffling, challenging for the ball or playing the ball. All other activity was classed as low intensity activity. An inter-operator reliability study revealed the system had a very good strength of agreement ( = 0.885). The times at which goals were scored were used to determine the percentage of time players spent performing high intensity activity (%HI) when their team was level, ahead and behind. There were only two players whose team was level, ahead and behind for at least 10 minutes during the match observed. Therefore, two separate analyses were done; one on the 12 players whose teams were level and ahead for at least 10 minutes and one on the 7 players whose teams were level and behind for at least 10 minutes. Wilcoxon signed ranks tests were used to compare the %HI between score-line states. Results & Discussion The 12 players whose teams were level and ahead had similar %HI when level and ahead (9.4+2.5% v 8.8+2.5%, p > 0.05). The second group of 7 players spent had %HI of 8.3+1.9% when level which was significantly greater than the 7.1+1.8% when behind (p < 0.01). The difference between %HI in the level and behind score-line states agrees with previous research (1) but the non-significant difference between level and ahead score-line states does not. Conclusion There is evidence that score-line continues to influence work-rate in soccer. Further research is needed to explore the mechanisms of score-line effect on work-rate.